A Comparative Study of Three Min Respiratory Exercise Test & Six Min Walk Test as a Means to Score Breathlessness in COPD Patients and Normal Healthy Individuals - Shweta A. Panchbudhe1 , Umanjali Damke2 , Anjalee Chiwhane3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2011 update recommends thatthe management and treatment of COPD be made to combine the impact of disease and future risk ofexacerbation.Objectives: The aim of the study was to compare 3MRET & 6MWT as a means to score breathlessnessin COPD patients & normal healthy individuals along with to analyse and compare POD index of 3MRET& walking POD index of 6MWT in COPD patients, normal healthy individuals and to analyse whetherPOD index of 3MRET or walking POD index of 6MWT is a better means to score breathlessness in COPDpatients when compared with normal healthy individuals.Material and Method: It was observational comparative study conducted in respiratory Physiotherapy setup on 45 Normal healthy individuals and 45 COPD patients between the age group 30-50 years.Results: Study found that there is a statistically highly significant difference between POD index of 3MRETand walking pod index of 6MWT in COPD patients. There is a statistically highly significant differencebetween the POD index of 3 MRET and walking pod index of 6MWT in normal healthy individuals. MRETis a better means to score breathlessness in COPD patients as compared to normal healthy individuals. It wasfound that 3MRET is a better means to score breathlessness as compared to 6 min walk test